Polish Partisan Formations during 1942–1944 in Jewish Testimonies - Aleksandra Bańkowska (Zagłada Żydów)
This article aims to present the picture of Polish partisans in the accounts of Jewish survivors, based on materials from the Archive of the Jewish Historical Institute. This texts discusses the following Polish underground military formations: the Home Army, Peasants' Battalions, socialist armed groups, the National Armed Forces and the People's Guard /Army (GL/AL). In her discussion of pro-independence armed formations, the author emphasises. the feeling of danger still present in those accounts, fear of death even from the partisans. The accounts mention a number of murders as well as difficulties Jews encountered when they wanted to join partisan outfits, not to mention refusals of co-operation from Poles. Testimonies about GL/AL differ from previous ones by their “insider” perspective, as most of them come from Jews, GL partisans. Perhaps that is why they are dominated by a favourable picture of communist partisans, even though several accounts mention conflicts between the commanders and the Jewish GL partisan outfits